2019
DOI: 10.3390/su11061688
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Caregivers’ Nutrition Knowledge and Food Market Accessibility on Preschool Children’s Dietary Diversity in Remote Communities in Southeast Nigeria

Abstract: Empirical evidence is scanty on the nexus between caregivers’ nutrition knowledge, market accessibility, and preschool children’s dietary diversity in remote communities of Africa’s most populous country, Nigeria. To fill this gap, this study evaluated the effects of caregivers’ nutrition knowledge and access to food market on dietary diversity of preschool children. We used cross-sectional data from four hundred households selected from twenty remote communities in Southeast Nigeria. The study adopted instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…Moreover, even if they are not able to provide the adequate meal, they provide the possibility of obtaining it, as in the other Polish study that presented a lower frequency of having school lunch prepared at home for the children of single mothers, than for others, but at the same time providing their children resources to buy it at school [23]. However, a lack of nutritional knowledge may be a problem, as it is an important determinant [24], which was also evident from the example of pregnant single mothers who tend to have a lower nutritional value of their diet but also smoke cigarettes compared with the reference group of other pregnant women [25]. Also, the recent study by Boccia et al [26] indicated that for consumers, their perception and awareness may be crucial while making purchase decisions.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, even if they are not able to provide the adequate meal, they provide the possibility of obtaining it, as in the other Polish study that presented a lower frequency of having school lunch prepared at home for the children of single mothers, than for others, but at the same time providing their children resources to buy it at school [23]. However, a lack of nutritional knowledge may be a problem, as it is an important determinant [24], which was also evident from the example of pregnant single mothers who tend to have a lower nutritional value of their diet but also smoke cigarettes compared with the reference group of other pregnant women [25]. Also, the recent study by Boccia et al [26] indicated that for consumers, their perception and awareness may be crucial while making purchase decisions.…”
Section: Discussionmentioning
confidence: 94%
“…These results were in line with the findings of previous researchers on nutritional knowledge enhancement after training and healthy eating habits. For instance, the findings of Audu (2013), Onyeneke, Nwajiuba, Igberi, Amadi, Anosike, Oko-Isu., Munonye, Uwadoka, and Adewale (2019) corroborates the outcome of this study as they found out that nutrition education is an effective means of alerting of individuals of the need for nutrition improvement and step towards improving food habits. Also, Baker, Simpson, Lloyd, Bauman, and Singh (2011), Barte et al, (2011), and Wadden, Webb, Moran, and Bailer (2012) confirmed the effectiveness of lifestyle modifications in helping individuals to resolve the problem of obesity-related comorbidities, improved the effectiveness of diet and weight management.…”
Section: Discussionmentioning
confidence: 99%
“…attitudinal and behavioral change in the individual. Nutrition education has been reported to be one of the effective means of alerting of individuals of the need for nutrition improvement and step towards improving food habits (Audu, 2013;Onyeneke, Nwajiuba, Igberi, Amadi, Anosike, Oko-Isu., Munonye, Uwadoka,. & Adewale, 2019 ).The ultimate goal of nutrition education according to leverton (1974), is to aid individual to effectively apply nutritional knowledge, attitudes beliefs and practices and modify their diets.…”
Section: Introductionmentioning
confidence: 99%
“…Food frequency data was collected for all foods consumed in the household and the data was used to compute the dietary diversity of each household as a measure for nutrition. This index-dietary diversity score-is a metric for measuring nutritional quality of households and individuals [35][36][37] and impacts of nutrition interventions [38].…”
Section: Sampling Procedures and Data Collectionmentioning
confidence: 99%
“…We adopted the Food and Nutrition Technical Assistance (FANTA) guide in computing the dietary diversity score of households. This guide classifies foods consumed by human beings into twelve broad categories which is a reflection of nutrition and dietary quality [35,39]. The various classes of food according to FANTA are "cereals/grains, fish and seafood, root/tubers and plantain, seeds/pulses/nuts, vitamin A-rich fruits and vegetables, other fruits and vegetables, milk and milk products, oil/fats, meat (organ and flesh meat) and edible insects, sugar/honey, eggs, miscellaneous (spices, condiments and beverages)" [39,40].…”
Section: Household Dietary Diversity Indicatormentioning
confidence: 99%